2017
DOI: 10.1007/s11418-017-1089-2
|View full text |Cite
|
Sign up to set email alerts
|

Two new antimalarial quassinoid derivatives from the stems of Brucea javanica

Abstract: Phytochemical investigation of the stems from Brucea javanica led to the isolation of two new quassinoids, brujavanol C (1) and brujavanol D (2), together with six known compounds (3-8). The chemical structures were elucidated by means of various spectroscopic methods. All the isolated compounds were evaluated for antimalarial activity against Plasmodium falciparum and compounds 6 and 7 exhibited the most potent activity against the K1 strain, with IC values of 1.41 and 1.06 μM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Bruceine D ( 303 ) was also isolated from the roots of the plant. Both compounds inhibited P. falciparum K1 strain, but 303 was also cytotoxic against cancerous human KB and NCI-H187 cells [188, 189]. Eurycoma longifolia (Simaroubaceae) root extract yielded the new 18-dehydro-6α-hydroxyeurycomalactone ( 305 ), alongside known eurycomanone ( 306 ) and eurycomanol ( 307 ), with nanomolar antiplasmodial activity [86].…”
Section: Terpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruceine D ( 303 ) was also isolated from the roots of the plant. Both compounds inhibited P. falciparum K1 strain, but 303 was also cytotoxic against cancerous human KB and NCI-H187 cells [188, 189]. Eurycoma longifolia (Simaroubaceae) root extract yielded the new 18-dehydro-6α-hydroxyeurycomalactone ( 305 ), alongside known eurycomanone ( 306 ) and eurycomanol ( 307 ), with nanomolar antiplasmodial activity [86].…”
Section: Terpenesmentioning
confidence: 99%
“…Eurycoma longifolia (Simaroubaceae) root extract yielded the new 18-dehydro-6α-hydroxyeurycomalactone ( 305 ), alongside known eurycomanone ( 306 ) and eurycomanol ( 307 ), with nanomolar antiplasmodial activity [86]. The bioactivity of quassinoids has been correlated with the presence of an α,β-unsaturated ketone in ring A. Quassinoids possessing an oxymethylene bridge joining C-8 and C-13 have also shown pronounced activity [188]. These two structural features are considered essential for potent antiplasmodial activity but might also be responsible for the cytotoxicity of the compounds.…”
Section: Terpenesmentioning
confidence: 99%
“…6 Because of the use of Kniphofia reflexa Hutchinson ex Codd. Asphodelaceae in the treatment of relapsing fevers, supported by literature data on the antiplasmodial activities within classes of natural products like terpenes, [7][8][9][10] flavonoids, [11][12][13] alkaloids, [14][15][16][17] quassinoids, 7,18 xanthones, [19][20][21][22] quinones, and anthraquinones, [23][24][25][26][27][28][29] a needed study of this plant was conducted considering its unique endemic nature, coupled to its classification. To the best of our knowledge, no study is reported on the antiplasmodial and antimalarial potential of chemical constituents of K reflexa.…”
Section: Introductionmentioning
confidence: 99%